2022
DOI: 10.1002/rcs.2450
|View full text |Cite
|
Sign up to set email alerts
|

The intraoperative use of augmented and mixed reality technology to improve surgical outcomes: A systematic review

Abstract: Background This systematic review aims to critically appraise the intraoperative use of augmented and mixed reality technology to improve surgical outcomes. Method A literature search of PubMed, Scopus, Cochrane Central Register of Controlled Trials, http://ClinicalTrials.gov and WHO ICTRP was performed in accordance with Cochrane Handbook for Systematic Reviews of Interventions. Results This review included 94 studies on 2473 patients, comprising 78 studies on augmented reality and 16 on mixed reality. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 152 publications
(289 reference statements)
0
6
0
Order By: Relevance
“…Both technologies have made remarkable progress and are used not only in video games but also in everyday life, including industries such as construction and manufacturing. Reports of the application of VR are gradually increasing in medicine [13,14]. However, there are few studies on the application of VR and MR in LLR [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both technologies have made remarkable progress and are used not only in video games but also in everyday life, including industries such as construction and manufacturing. Reports of the application of VR are gradually increasing in medicine [13,14]. However, there are few studies on the application of VR and MR in LLR [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Additional research and development are needed to optimize the application of this technology and explore its full potential. Although there have been indications of its usefulness, the number of studies are few [10][11][12][13][14]. Previous studies have shown that the combination of XR technology with laparoscopic cholecystectomy performed by mid-career surgeons contributed to a decrease in blood loss and complication rates [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, a growing number of AR applications have been used in training, education, telemedicine, preoperative planning and postoperative assessment, and intraoperative systems. [4,5]. For instance, AR HMDs enable capturing of images and videos from a surgeon's perspective and share them with remote users [6].…”
Section: Introductionmentioning
confidence: 99%
“…The challenges include integrating AR technology seamlessly into clinical workflows, ensuring patient safety and privacy, and overcoming technical limitations such as accuracy and field of view [ 5 , 6 ]. Despite these challenges, a growing number of AR applications have been used in training, education, telemedicine, preoperative planning and postoperative assessment, and intraoperative systems [ 7 , 8 ]. For instance, AR HMDs enable capturing of images and videos from a surgeon’s perspective and share them with remote users [ 9 ].…”
Section: Introductionmentioning
confidence: 99%